MACHINE LEARNING MODEL EVALUATION AND METHODOLOGY FOR PREPARING MODELS FOR DEPLOYMENT - Matchonov, Shohrukh; Pulatova , Sarvinoz (Uzbekistan Open Conference, 2025)
This paper develops methodological approaches to evaluating machine learning models within Business Intelligence (BI) systems, analyzing their accuracy levels, and preparing them for deployment. The study examines both offline and online model evaluation techniques, discusses strategies for preventing overfitting and underfitting, and assesses the effectiveness of train-test split and cross-validation methods.
Keywords: machine learning; BI systems; evaluation; cross-validation; model preparation; overfitting